(untitled) (Baghdad Science Journal, 2005)
During the study the current selection seven stations in the Zab River bottom and the Tigris River took samples a month to study the signs of bacterial contamination study coliform and colon fecal Almsobhaat and Almsobhaat Bazah and the total number of bacteria and bacterial gangrene gas causing Knkeran as well as a study to isolate and diagnose some races and types of bacterial pathogens in water or intensityusing the traditional system and the system of intestinal bacteria